Peran Manajemen Karir dalam Proses Peningkatan Kinerja Karyawan dalam Suatu Perusahaan - Zelda Palin Ma'dika; Hayatul Khairul Rahmat (Journal of Current Research in Management, Policy, and Social Studies, 2024)
Human resources (HR) are one of the important elements that play a direct role in organizational operations to achieve predetermined goals. A good organization that has a positive reputation in the eyes of society will not ignore aspects of developing the quality of its human resources. Therefore, HR management plays a very significant role in organizations. One of the functions of HR management is to develop careers and increase work motivation in order to achieve employee job satisfaction and optimal results.This research uses library research methods. library research is a bibliographic research method carried out scientifically and systematically. This includes collecting bibliographic materials relevant to the research object, using data collection techniques through bibliographic methods, as well as organizing and presenting the data obtained.Career planning is an organized process for planning and managing an individual''s career development within a specified time period. This process includes identifying career goals, evaluating individual strengths and weaknesses, and formulating concrete steps to achieve these goals. The objectives of career management: to achieve employee and company goals, show concern for employee welfare, support employees in recognizing their talents and skills, build close relationships between employees and the company, prove commitment to social responsibility, and increase effectiveness in achieving goals company.Based on the results of the discussion, it can be concluded that career management, which is included in human resource management (HR), plays a very important role in achieving successful results with a structured process. The application of career management provides many benefits, this can encourage individual growth to be able to develop themselves, this will also make it easier to achieve employee and company goals.